Can details depoliticize? An examination of the formalization strategy - Hansen, Jesper Asring (Public administration (London), 2024)
Political superiors bestow legitimacy on decisions when delegating authority to agencies. Yet, research convincingly demonstrates that the delegation of authority to agencies does not guarantee depoliticized decisions. political principals with the intent of signaling depoliticization may limit agency discretion by invoking a formalization strategy: a strategy where the principal details what constitutes a legitimate decision. The argument of this study is that this strategy falls short in achieving depoliticization, because agencies have incentives to accommodate key voters' opinions, especially in resourceful constituencies. I test the argument by analyzing decisions made by the United Kingdom's Office for Standards in Education—an agency subject to strong formalization requirements when making decisions. In support of the argument, I find that key voters' opinions predict decisions more strongly than any of the other items specified by the political principal, and that voters' opinions matter more in constituencies with high mobilization potentials.